Экспертная система поиска неисправностей - Шмонин, А. Ю. (ХНУРЕ, 2012)
This work is devoted to the development of expert system troubleshooting. The developed software provides the ability to quickly detect the failure of a typical laser printer.
Keywords: экспертная система; поиск неисправностей